Green synthesis of CuFe₂O₄ nanoparticles: Multifunctional applications in electrochemistry, sensing and photocatalysis - N. Raghavendra; Nagaswarupa H P; Shashi Shekhar T R; M. Mylarappa; Basavaraju N; Surendra B S (Next Materials, 2025)
We successfully synthesized nanostructured copper ferrite (CuFe2O4) using a combustion process with eco-friendly, renewable fuels derived from Aloe vera and Flacourtia indica plant root extracts. The structural, morphological, and compositional properties of the synthesised CuFe2O4 nanoparticles were thoroughly characterised using advanced techniques, including scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and energy-dispersive X-ray spectroscopy (EDX). Electrochemical performance was evaluated through cyclic voltammetry (CV), AC impedance, and galvanostatic charge-discharge (GCD) measurements in a 0.1 M HCl electrolyte. Additionally, the nanoparticles were tested for their sensing capabilities toward chemical sensors (arsenic trioxide and mercuric acetate) and photocatalytic activity under UV light. Remarkably, CuFe2O4 nanoparticles synthesized with Aloe vera demonstrated superior photocatalytic efficiency, degrading 95.6 % of Rhodamine B (RhB) dye within 120 min, compared to 82 % degradation achieved using the plant root extract. The magnetic recoverability of CuFe2O4 nanoparticles further enhances their potential as an efficient and reusable photocatalyst. This study highlights the synthesis of high-quality, reproducible, and environmentally benign bio-composite materials, paving the way for sustainable and non-toxic applications in catalysis and sensing.